Cultural code-switching in high context global virtual team members: A qualitative study. (December 2022) - Zakaria, Norhayati; Ab Rahman Muton, Nursakirah
Global virtual teams (GVTs) are a prevalent work structure that enable people to accomplish tasks across time, space, and cultural boundaries and perform cross-culturally. However, few studies have highlighted what exact behaviors enable GVTs to share knowledge effectively. Based on a qualitative study using semi-structured interviews with 22 respondents from various multinational corporations (MNCs) in Malaysia, we answer the following overarching research question: Why do high context members switch their communicative behaviors amongst foreign team members within global virtual teams? Our study provides detailed narratives of high-context team members becoming the behavioral "switchers" to collaborate and share knowledge with their foreign team members effectively. Our study defines and clarifies the concept of cross-cultural code-switching as a key behavior reflecting effective cross-cultural performance when accommodating foreign team members' communicative behaviours by adopting (1) directness in speech, (2) openness during knowledge sharing, and (3) task-oriented aims. This study addresses several gaps in the field of cross-cultural management by extending Hall's (1976) theoretical lens on high-context and low-context cultures, Molinsky's (2007) cross-cultural code-switching concept in the context of the virtual work structure, and the criterion space surrounding cross cultural performance.